Does Foreign Direct Investment Affect Labour Productivity in the Automotive Industry? The Czech Republic Case Study - Moravcová, Martina; Janíčko, Martin, 1983-; Svoboda, Miroslav; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
The aim of this thesis is to show effects of foreign direct investment on labour productivity in Czech automotive sector in the period 2004-2009. The effects are measured through horizontal spillovers (technology transfer) representing the influence of foreign firm on Czech automotive sector and through Herfindahl index representing market concentration in the automotive sector. Based on models used in this thesis I have found out that between labour productivity and technology transfer of foreign firms in the automotive sector is not significant relationship, but labour productivity is positively and significantly influenced by market concentration in the sector. These findings do not correspond fully to widespread opinion that foreign direct investments enhance labour productivity of domestic firms by bringing new knowledge or technology. These findings correspond only to the hypothesis that higher concentration of the sector caused by foreign presence positively influence labour productivity.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses